$k$-cordial Labeling of Triangular Belt, Alternate Triangular Belt, Braid Graph and $Z$-$P_n$ - N. B. Rathod; K. K. Kanani (International Journal of Mathematics And its Applications, 2017)
In this research paper, we find $k$-cordial labeling of some special graphs. We prove that Triangular Belt $TB(n)$$(\downarrow^n)$, Alternate Triangular Belt $ATB(n)$$(\downarrow\uparrow\downarrow\uparrow...)$ and Braid Graph $B(n)$ are $k$-cordial. Moreover, the graph $Z$-$P_{n}$ is $k$-cordial for all odd $k$.